Oxidative Stress in Autistic Children Alters Erythrocyte Shape in the Absence of Quantitative Protein Alterations and of Loss of Membrane Phospholipid Asymmetry. (11th November 2018) - Bolotta, Alessandra; Battistelli, Michela; Falcieri, Elisabetta; Ghezzo, Alessandro; Manara, Maria Cristina; Manfredini, Stefano; Marini, Marina; Posar, Annio; Visconti, Paola; Abruzzo, Provvidenza Maria
Abstract : Red blood cells (RBCs) from people affected by autism spectrum disorders (ASDs) are a target of oxidative stress. By scanning electron microscopy, we analyzed RBC morphology from 22 ASD children and show here that only 47.5 ± 3.33% of RBC displayed the typical biconcave shape, as opposed to 87.5 ± 1.3% (mean ± SD) of RBC from 21 sex- and age-matched healthy typically developing (TD) controls. Codocytes and star-shaped cells accounted for about 30% of all abnormally shaped ASD erythrocytes. RBC shape alterations were independent of the anticoagulant used (Na2 -EDTA or heparin) and of different handling procedures preceding glutaraldehyde fixation, thus suggesting that they were not artefactual. Incubation for 24 h in the presence of antioxidants restored normal morphology in most erythrocytes from ASD patients. By Coomassie staining, as well as Western blotting analysis of relevant proteins playing a key role in the membrane-cytoskeleton organization, we were unable to find differences in RBC ghost composition between ASD and normal subjects. Phosphatidylserine (PS) exposure towards the extracellular membrane domain was examined in both basal and erythroptosis-inducing conditions. No differences were found between ASD and TD samples except when the aminophospholipid translocase was blocked by N-ethylmaleimide, upon which an increased amount of PS was found to face the outer membrane in RBC from ASD. These complex data are discussed in the light of the current understanding of the mode by which oxidative stress might affect erythrocyte shape in ASD and in other pathological conditions.